Pengaruh Relaksasi Benson dan Aromaterapi Lemon terhadap Penurunan Skala Nyeri pada Pasien Sindrom Koroner Akut di Ruang Anggrek - Hanun Nazih, Hanun Nazih; Ahmad Ikhlasul Amal; Dwi Retno Sulistyaningsih (Pusat Riset dan Inovasi Nasional, 2025)
Acute coronary syndrome (ACS) is one of the leading causes of death worldwide and remains a serious health problem characterized by chest pain due to narrowing or blockage of the coronary arteries. Pain experienced by ACS patients can affect both physiological and psychological conditions, therefore prompt and appropriate management is required. In addition to pharmacological therapy, non-pharmacological interventions such as relaxation techniques and aromatherapy can serve as alternatives to help reduce pain intensity. This study aimed to determine the effect of combining Benson relaxation and lemon aromatherapy on pain scale reduction among ACS patients in the Anggrek Ward of RSUD dr. H. Soewondo Kendal. The research employed a pre-experimental design with a one-group pretest-posttest approach. A total of 29 respondents were recruited using purposive sampling based on predetermined inclusion and exclusion criteria. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test because the data were not normally distributed. The results showed that the mean pain score before the intervention was 7.14 (moderate to severe pain), while after the intervention it decreased to 4.24 (mild to moderate pain). The Wilcoxon test revealed a significant difference between pain scores before and after the intervention (p = 0.000, p < 0.05). In conclusion, the combination of Benson relaxation and lemon aromatherapy was significantly effective in reducing pain among ACS patients. This intervention may be recommended as a non-pharmacological alternative to support acute pain management in patients with acute coronary syndrome.